2015
DOI: 10.1021/acsami.5b00448
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Quantum Dots and Applications in Photocatalytic Energy Conversion

Abstract: Quantum dots (QDs) generally refer to nanoscale particles of conventional semiconductors that are subject to the quantum-confinement effect, though other nanomaterials of similar optical and redox properties are also named as QDs even in the absence of strictly defined quantum confinement. Among such nanomaterials that have attracted tremendous recent interest are carbon dots, which are small carbon nanoparticles with some form of surface passivation, and graphene quantum dots in various configurations. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
360
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 655 publications
(367 citation statements)
references
References 119 publications
5
360
1
1
Order By: Relevance
“…Discovery of graphene further advanced the study of photoluminescence of carbon‐based materials in the context of exciting applications of graphene/carbon quantum dots (CQDs) in bioimaging,160, 161, 162 drug delivery,163 photocatalysis,164, 165 electrocatalysis,165 photovoltaics,166, 167 and sensing 168. Those CQDs169 are a new form of fluorescent carbon nanostructures.…”
Section: Applications Of the Photochemical Activity Of Nanoporous Carmentioning
confidence: 99%
“…Discovery of graphene further advanced the study of photoluminescence of carbon‐based materials in the context of exciting applications of graphene/carbon quantum dots (CQDs) in bioimaging,160, 161, 162 drug delivery,163 photocatalysis,164, 165 electrocatalysis,165 photovoltaics,166, 167 and sensing 168. Those CQDs169 are a new form of fluorescent carbon nanostructures.…”
Section: Applications Of the Photochemical Activity Of Nanoporous Carmentioning
confidence: 99%
“…At higher temperature (195°C), a yellow-colored solution was obtained and a bright fluorescence was detected. However, the EG solution also emitted a detectable fluorescence even without addition of SiCl 4 , indicating the formation of fluorescent carbon nanoparticles under this condition [56,57]. All results indicate that the fluorescent SiNRs with lengths of approximately 500 nm and diameters of approximately 50 nm could be prepared via the EG-mediated process at 160°C for 6 h, in which EG not only acts as solvent but also as reducing and coordinating reagent for the reaction.…”
Section: Polymerizationmentioning
confidence: 75%
“…2. The peak at 1534 cm À1 was attributed to the bending vibrations of NAH, 1562 cm À1 belonged to stretching vibrating of C@C, meanwhile peaks at 1651 and 1700 cm À1 were assigned to the stretching vibrations of C@O in ketone and amido, respectively [35,38]. No obvious characteristic peaks assigned to imidazolium could be found in the FT-IR spectrogram, which strongly suggested that ionic liquids can be easily removed from as-obtained samples.…”
Section: Resultsmentioning
confidence: 92%
“…The unique properties of stabilities, biocompatibility, nontoxicity and the strong fluorescence promise a potential application for the novel water-soluble carbon nanomaterial. In addition, results of previous researches indicate that CQDs modified on semiconductor photocatalysts can enhance the capacity of light absorption to utilize more of the full spectrum of the sunlight and accelerate the transfer of photo-induced electrons to suppress the rapid recombination of the charge carriers that have been transmitted to the surface of the semiconductors [35]. However, it still needs to explore that how to introduce the CQDs to the semiconductor by evenly disperse it on the surface of the semiconductor.…”
Section: Introductionmentioning
confidence: 99%